Classification of Brain MRI Images and Cellular Localization Analysis - Ashwin Chavan, Prof. Sandeep Vanjale (Cuestiones de Fisioterapia, 2025)
Brain Tumor is a type of disease in which brain cells get abnormal growth which causes harm to the person if not detected early. But even if it is detected it sometimes gets hard to identify the location of the cells. If it is found, then proper treatment can be provided to the patient to treat the disease. It is because the brain is the most important part of our organ system which if not treated properly can make a person in a coma or worse condition. Accurately identifying the location is the most important while diagnosis of brain tumor.